Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review - Page 746: 50



Work Step by Step

$a^{-\frac{1}{4}}(a^{\frac{5}{4}}-a^{\frac{9}{4}})$ =$a^{-\frac{1}{4}}(a^{\frac{5}{4}})-a^{-\frac{1}{4}}(a^{\frac{9}{4}})$ =$(a^{-\frac{1}{4}+\frac{5}{4}})-(a^{-\frac{1}{4}+\frac{9}{4}})$ =$(a^{\frac{-1+5}{4}})-(a^{\frac{-1+9}{4}})$ =$(a^{\frac{4}{4}})-(a^{\frac{8}{4}})$ =$(a^{1})-(a^{2})$ =$a-a^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.